First do no harm: pain relief for the peripheral venous cannulation of adults, a systematic review and network meta-analysis. Issue 1 (December 2015) - Bond, Mary; Crathorne, Louise; Peters, Jaime; Coelho, Helen; Haasova, Marcela; Cooper, Chris; Milner, Quentin; Shawyer, Vicki; Hyde, Christopher; Powell, Roy
Abstract Background Peripheral venous cannulation is an everyday practice in hospitals, which many adults find painful. However, anaesthesia for cannulation is usually only offered to children. Inadequate pain relief is not only unpleasant for patients but may cause anxiety about further treatment and deter patients from seeking medical care in the future. The aim of this study is to discover the most effective local anaesthetic for adult peripheral venous cannulation and to find out how the pain of local anaesthetic application compares with that of unattenuated cannulation. Methods These aims are addressed through a systematic review, network meta-analysis and random-effects meta-analysis. Searching covered 12 databases including MEDLINE and EMBASE from 1990 to August 2015. The main included study design was RCTs. The primary outcome measure is self-reported pain, measured on a 100 mm visual analogue scale. Results The systematic review found 37 includable studies, 27 of which were suitable for network meta-analysis and two for random-effects meta-analysis. The results of the network meta-analysis indicate that none of the 17 anaesthetic considered had a very high probability of being the most effective when compared to each other; 2 % lidocaine had the highest probability (44 %). When the anaesthetics were compared to no treatment, the network meta-analysis showed that again 2 % lidocaine was estimated to be the most effective (mean difference −25.42 (95 % CI −32.25, −18.57). Other members of the 'caine' family were also estimated to be more effective than no treatment as were Ametop®, EMLA® and Rapydan® patch. The meta-analysis compared the pain of anaesthetic application with the unattenuated pain of cannulation. This found that all applications of local anaesthetic were less painful than cannulation without local anaesthetic. In particular a 1 % lidocaine injection was estimated to be −12.97 (95 % CI −15.71, −10.24) points (100 mm VAS) less painful than unattenuated cannulation. Conclusions The pain of peripheral venous cannulation in adults can be successfully treated. The pain of application of any local anaesthetic is less than that of unattenuated cannulation. Local anaesthetic prior to cannulation should become normal practice and a marker of high quality care. Protocol registration The protocol for the larger study was registered with PROSPERO no.CRD42012002093 .